Notes on a World with Generative AI - Nikos Askitas (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Generative AI (GenAI) and Large Language Models (LLMs) are moving into domains once seen as uniquely human–reasoning, synthesis, abstraction, and rhetoric. Addressed to labor economists and informed readers, this paper clarifies what is truly new about LLMs, what is not, and why it matters. Using an analogy to autoregressive models from economics, we explain their stochastic nature, whose fluency is often mistaken for agency. We situate LLMs in the longer history of human–machine outsourcing, from digestion to cognition, and examine disruptive effects on white-collar labor, institutions, and epistemic norms. Risks emerge when synthetic content becomes both product and input, creating feedback loops that erode originality and reliability. Grounding the discussion in conceptual clarity over hype, we argue that while GenAI may substitute for some labor, statistical limits will preserve a key role for human judgment. The question is not only how these tools are used, but which tasks we relinquish and how we reallocate expertise in a new division of cognitive labor.
Keywords: J24; O33; O31; J22; D83; L86; J44; O38; 330; generative artificial intelligence; large language models; autoregressive models; labor economics; technological change; automation and outsourcing; human–machine collaboration; knowledge work; epistemic norms; digital transformation